Spectrum Monitoring In OFDM-Based Cr Networks By Window Based Energy Ratio Algorithm (International Journal of Engineering and Computer Science, 2017)
This work presents a spectrum monitoring algorithm for OFDM based cognitive radios and in this, monitoring algorithm the primary user reappearance can be detected during the secondary user transmission. The proposed technique reduces the frequency with which spectrum sensing must be performed and greatly decreases the elapsed time between the start of a primary transmission and its detection by the secondary network. The analysis and simulation show that the algorithm can effectively and accurately detect the appearance of the primary user